Building a united community: Reading the Johannine concept of unity through the eyes of an Akan - Gharbin, Godibert K.; Van Eck, Ernest (Hervormde teologiese studies, 2023)
From the 1960s, African theologians sought to decolonise biblical scholarship, calling for a hermeneutical approach that pays attention to the African sociocultural context – inculturation. One of the undergirding principles of inculturation is that there are African sociocultural questions that the Bible can address through the appropriate interpretative methodology. Thus, this culminated in the application of inculturation on different levels. Similarly, an analysis of Akan aphorisms – the anthology of valuable data on Akan anthropology and communitarian egalitarianism – and the Johannine theology of unity reveals that there are sociocultural maladies that require inculturation. Consequently, the study employed Ukpong’s inculturation hermeneutics to read the Johannine unity ideation because it facilitates the cross-pollination of ideas – the Johannine unity ideation to critique the Akan culture and the conceptualisation of unity in Akan proverbial lore to enrich the understanding of the Johannine theology of unity. The findings indicated that Akan unity ideation receives its impetus from personal and communal benefits, making sustainability impossible without them. Additionally, it contravenes the tenets of Akan communalism and anthropology. Furthermore, it revealed that Christian unity is grounded on replicating the divine community; therefore, it can fill the lacunae in the Akan concept. Finally, it established that the culture enriches the text.Contribution: Given that this article is an interactive engagement between the Johannine and Akan concepts of unity, it contributes to the ongoing discussions on contextual theology – the inculturation of the New Testament in the African context. Furthermore, it contributes to the discussions on Akan communalism.